ANALYSIS OF INFLAMMATORY CHANGES OF ENTHESES AND SYNOVIAL STRUCTURES IN PATIENTS WITH PSORIASIS AND PSORIATIC ARTHRITIS - Zhdan, V.M.; Tkachenko, M.V.; Babanina, M.Y.; Volchenko, H.V.; Kіtura Y.M.; Ivanitskiy, I.V.; Kyrian, O.A. (World of Medicine and Biology, 2023)
The study presents data on the relationship between clinical manifestations and signs of enthesitis, synovitis, and tendinitis detected during ultrasonography in patients with the cutaneous form of psoriasis and psoriatic arthritis. 56 patients with widespread psoriasis whom dermatologists first referred to a rheumatologist for joint and muscle pain were examined. The period of musculoskeletal pain in patients did not exceed 10 months. In addition to general clinical and laboratory examinations, all patients underwent ultrasonography of swollen and/or painful joints, tendons and ligaments. The study demonstrated the diagnostic capabilities of ultrasound to detect foci of inflammation in patients with psoriatic arthritis and identify groups of patients with isolated enthesitis and a combination of enthesitis with synovitis for differentiated anti-inflammatory therapy.